Explosive driven shock tube loading of aluminium plates: experimental study. (December 2015) - Louar, M.A.; Belkassem, B.; Ousji, H.; Spranghers, K.; Kakogiannis, D.; Pyl, L.; Vantomme, J.
Abstract: To accurately identify the material characteristics in material testing, the control of the initial and boundary conditions is very important. Among these conditions, obtaining a repeatable and known loading is a sensitive point especially for tests in the dynamic and impulsional range. Several techniques are used to generate blast wave loads. This paper focuses on the use of an explosive driven shock tube (EDST). The results of a series of tests using an EDST are discussed, with regard to the pressure, the impulse, the wave planarity and the repeatability of the loading. The EDST and free air blast are used to generate blast loading on fully clamped square aluminium plates. The response from both loads is measured with a high-speed 3D digital image correlation (DIC) system and compared to each other. The DIC measurements are compared to strain gauge measurement for validation purposes. It is found that EDST allows to reach higher levels of pressure and impulse than the free air blast leading to higher deformations and strain rates. It is also observed that the EDST tests show a higher repeatability and symmetry relative to the free air blast tests. Highlights: The blast wave generated by an EDST is investigated in terms of pressure, impulse and distribution. The blast response of aluminium plates is experimentally assessed. The response of the plate to EDST load is compared with free air blast tests. The results show that the EDST generates higher strains and strain rate than the free air blasts. The EDST offers a better repeatability in the tests.